Propolis extract in postharvest conservation Solo papaya cv. 'Golden' - Passos, Flávia Regina; Mendes, Fabrícia Queiroz; Pinto, Marina de Carvalho Eufrásio; Araújo, Emiliane Andrade; Carvalho, André Mundstock Xavier de (Semina: Ciências Agrárias, 2016)
The high perishability of papaya (Carica papaya L.) reduces its lifespan as well as limits marketing. Coating the fruits is an alternative to aid food preservation. We aimed to evaluate the effects of coating propolis extract on the physicochemical characteristics of papaya stored at room temperature. Solo papayas cv. 'Golden' were randomly divided into five postharvest treatment groups, three forms of dip-coating (70% alcohol, hydroalcoholic extract of propolis to 2.5%, and hydroalcoholic extract of propolis to 5%) and two controls (one uncoated and one with refrigerated uncoated fruits). The weight loss, firmness, soluble solids (SS), titratable acidity (TA), SS/TA, and hydrogen potential (pH) were evaluated at the intervals of 4 days every 12th storage day. Sensory analysis was performed on the 4th day of storage of papayas and evaluated by untrained through the acceptance testing. Treatments "refrigerated", "propolis 2.5%", and "5% propolis" presented with the lowest weight loss. The firmness level for treatment propolis 5% was superior to that of control, alcohol, and 2.5% propolis treatments. The SS was greater for propolis 5% treatment, which only differed from the alcohol treatment. The TA and SS/TA did not vary with the treatments, but with the storage time. The pH of refrigerated papaya showed significant differences in relation to other treatments. The fruits subjected to refrigerated treatment presented with chilling injury. Papayas coated with propolis extract showed sensory acceptability similar to that in other treatments on the 4th day of storage. The coating of propolis extract is a promising alternative for the control of weight loss and for the maintenance of firmness in Solo papaya cv. 'Golden'.